Desain Model Bahan Ajar Berbasis Elektronik dan Minat Belajar Pendidikan Agama Islam Siswa Sekolah Dasar Negeri (SDN) Kelas Bawah di Indonesia - Muhammad Nasir; Saifun Nizar Alkhury; Muhammad Khairul Rijal (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2021)
Abstract Religious learning in the era of information technology development, especially in formal education institutions, faces serious challenges, if the teaching materials used are the majority of printed teaching materials and teacher teaching strategies are more dominant in applying a teacher-centered approach. Thus, in this millennial era, teachers are required to be more creative and innovative in developing and designing teaching materials, media, and student-centered learning strategies to increase motivation and interest in learning. This study aims to design an electronic-based Islamic Religious Education (PAI) teaching material model to increase student interest in elementary school (SDN) in Indonesia. Theories related to this design are the characteristics of the content and teaching materials of Islamic Religious Education, constructivist learning theory, technological and humanistic curricula as well as the characteristics of lower grade Public Elementary School (SDN) students. The type of research used is research and development with data collection techniques, interviews, and observations. The research findings show that the results of limited trials and extensive trials of the design of the electronic-based teaching material model of the development results indicate a significant increase in the learning interest of low-grade Public Elementary School (SDN) students in the subject of Islamic Religious Education (PAI) after the treatment. (µ ≤ 0.05).